Determination of Iron in Licorice Samples by Slotted Quartz Tube Flame Atomic Absorption Spectrometry (FAAS) with Matrix Matching Calibration Strategy after Complexation with Schiff Base Ligand-Based Dispersive Liquid-Liquid Microextraction - Kasa, Nursu Aylin; Bakirdere, Emine Gulhan (TAYLOR & FRANCIS INC, 2021)
In this study, a slotted quartz tube flame atomic absorption spectrometry (FAAS) system has been developed for the determination of iron after dispersive liquid-liquid microextraction. The iron coordinate complex was formed by using a ligand synthesized from the reaction of o-phenylenediamine and 5-bromosalicylaldehyde. Using the optimum conditions, the relative standard deviation was found to be 1.7% calculated from the lowest concentration of calibration plot, and the limits of detection and quantification were found to be 5.3 and 17.4 mu g L-1, respectively. Other figures of merit of the developed method were satisfactory and an approximate 48-fold enhancement in detection power was recorded compared to the conventional FAAS system. The developed method was applied to licorice samples to evaluate the accuracy and applicability to real samples. The recovery values were in the range from 88% to 106% with low standard deviations.
Keywords: Dispersive liquid-liquid microextraction; flame atomic absorption spectrometry (FAAS); iron; licorice; slotted quartz tube; CLOUD POINT EXTRACTION; PHASE MICROEXTRACTION; WATER; PRECONCENTRATION; FE; OPTIMIZATION; METHODOLOGY; CADMIUM; FOODS; ZN; Chemistry